Self-determination of indigenous peoples in Greenland : a comparison with the Orang Asli in Peninsular Malaysia - Hashimah Abdul Halim,; Rohaida Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
For many years, the indigenous peoples had been experiencing various acts of marginalisation and discrimination. However, to this day, the definitions and rights of the indigenous peoples in certain jurisdictions are still left ambiguous. These rights includes the right to self-determination which, on the surface, is linked to freedom to choose political status and cultural or economical development and can be considered as one of the vital rights for indigenous peoples as it allows the community to decide on various aspects of their lives. Looking beyond that, this concept can be further classified into external and internal self-determination and each country may adopt a different approach to this right. As Greenland has a relatively higher population of indigenous peoples, the laws and regulations on indigenous peoples can be distinct. Therefore, this study examines the availability of self-determination policies and possible issues on it’s implementation in Greenland in comparison to the rights of the Orang Asli in Peninsular Malaysia. By using critical legal analysis, this study provides an insight to the exercise of self-determination rights of the indigenous peoples in other jurisdiction and the relevancy of the same right in Malaysia which can help to identify certain aspects to be improved on in the existing national indigenous peoples’ rights laws.